Considerations in analysing elemental carbon from marine engine exhaust using residual, distillate and biofuels. (December 2018) - Aakko-Saksa, Päivi; Koponen, Päivi; Aurela, Minna; Vesala, Hannu; Piimäkorpi, Pekka; Murtonen, Timo; Sippula, Olli; Koponen, Hanna; Karjalainen, Panu; Kuittinen, Niina; Panteliadis, Pavlos; Rönkkö, Topi; et al.
Abstract: Elemental carbon (EC) concentrations in the exhaust of a medium-speed marine engine was evaluated using thermal-optical analysis (TOA). Particulate matter (PM) samples were collected at 75% and 25% engine loads using residual and distillate fuels with sulphur contents of 2.5%, 0.5% and 0.1%, and a biofuel (30% of bio-component). The EC analysis of PM samples from a marine engine proved to be challenging. For example, transformations of structure of the sampled particles in the inert and the oxygen mode were observed for marine engine exhaust samples. The relationship between constituents present in the samples from the marine engine using different fuels, and phenomena observed in the thermograms are discussed. Temperature protocol selection and sample pre-treatment (extractions and drying) affected the reported EC mass. Modifications in the methodology were suggested to increase the accuracy of the analysis. Repeatability and reproducibility of the EC analysis was studied in the round-robin of three laboratories. Highlights: EC analysis was challenging for marine engine exhaust samples. The behaviour observed in the thermograms changed depending on the fuel. Temperature protocol used and sample extraction affected the EC results. Interlaboratory round-robin of EC analysis showed differences between laboratories.